Tarifbindung und die ökonomische Rationalität von Lohnrigiditäten - Wolfgang Franz; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This study provides empirical evidence for the economic rationality of wage rigidities. Theoretically wage rigidities can result from contracts, implicit contracts, from efficiency wages and from insider-outsider behaviour. Based on a survey of 801 firms strong support has been found for explanations based on collective wage agreements and on efficency wages as well. Collective wage agreements and implicit contracts are important reasons for wage rigidities for the low skilled. Furthermore survey respondents indicate that the reduction of turnover costs, adverse selection and specific human capital in quits are important reasons for wage rigidities for high skilled labour. Compared to findings from the USA, in Germany collective wage agreements and firm specific human capital seem to be more important explanations.
Keywords: K31; J51; J41; J30; 330; Lohnrigiditäten; Arbeitsrecht; Tarifverträge; Effizienzlohntheorien; ?Insider-Outsider?-Theorien; Beschäftigung; Lohnrigidität; Effizienzlohn; Tarifpolitik; Arbeitsrecht; Insider-Outsider-Modell; Ungelernte Arbeitskräfte; Hochqualifizierte Arbeitskräfte; Beschäftigungseffekt; Schätzung; Deutschland